The Effect of Human Umbilical Cord Mesenchymal Stromal Cells in Protection of Dopaminergic Neurons from Apoptosis by Reducing Oxidative Stress in the Early Stage of a 6-OHDA-Induced Parkinson's Disease Model. Issue 1 (December 2019) - Chi, Heng; Guan, Yunqian; Li, Fengyan; Chen, Zhiguo
Oxidative stress is an important cause of dopaminergic (DA) neuron apoptosis in Parkinson's disease (PD). Mesenchymal stromal cells (MSCs) possess antioxidative features. In this study, we investigated whether MSCs could reduce oxidative stress and protect DA neurons from apoptosis by intravenous (I.V.) injection in the early stage of a 6-hydroxydopamine (6-OHDA)-induced PD model. MSCs were injected into the tail vein of mice, and behavioral tests, immunofluorescence staining, western blot, and oxidative stress levels were assessed at different time points. After 6-OHDA exposure, DA neuron apoptosis was detected, together with severe oxidative stress in brain and periphery. Compared with the non-transplanted sham controls, motor function in the 6-OHDA-lesioned group after I.V. injection of MSCs was significantly improved, and the levels of DA neuron apoptosis and oxidative stress decreased. The results demonstrate that MSCs can rescue DA neurons from ongoing apoptosis by reducing oxidative stress, and provide insights on developing new therapeutic strategies to offset the degenerative process of PD.